Tinjauan kriminologis terhadap kejahatan penganiayaan yang dilakukan oleh anak klithih di Daerah Istimewa Yogyakarta - Zainuri Zainuri; Yanto Yanto; Hartanti Hartanti (Universitas Janabadra, 2019)
This study aims to examine and analyze: the factors that led to the occurrence of crimes in the form of persecution Klithih in the Special Region of Yogyakarta and the efforts made by the Police to prevent and overcome the crimes committed by Pelaku Klithih in the Special Region of Yogyakarta. This study uses library research library research and field research. The nature of this research is descriptive. This study uses primary data and secondary data. Data collection is done by interview. Data analysis in this study used qualitative analysis. Based on the results of the study it was concluded that, the factors that caused the crime of abuse with random victims of persecution, among others, were family factors that were not harmonious for the perpetrators, because parents were divorced. Most children are raised by one of the parents only or taken care of by their grandparents, then the freedom or control of parents is lacking, especially in association after the learning process in the school, the influence of technology in the form of vehicles that are capable and easy to get, poorly controlled and negatively impacted communication tools, juvenile psychologists in the transitional period both biologically and socially, legal sanctions that do not cause a deterrent shock therapy effect for child offenders, as well as Polri efforts in overcoming this crime, including involving persuasive, pre emptive efforts preventive and repressive form of punishment for cases of severe children. Forms of guidance to school schools in Yogyakarta, joining Ceremonial training every Monday, other counseling efforts, patrolling during school hours by targeting school children who are playing truant, hanging out during school hours, and investigating and investigating events that occur involving both child perpetrators and victims, with existing techniques and Standard Operating Procedure.